Phase equilibria, structural and thermodynamic properties of phases in the nickel (II) methanesulfonate – Water, cobalt (II) methanesulfonate – Water and manganese (II) methanesulfonate – Water systems. (July 2023) - Belova, Ekaterina V.; Shakirova, Julia D.; Lyssenko, Konstantin A.; Mikheev, Ivan V.; Maliutin, Alexey S.; Kovalenko, Nikita A.; Uspenskaya, Irina A.
Highlights: Solid-liquid equilibria in the Ni(CH3 SO3 )2 -H2 O, Co(CH3 SO3 )2 -H2 O, and Mn(CH3 SO3 )2 -H2 O systems were studied. Water vapor pressure was determined in the Ni(CH3 SO3 )2 -H2 O, Co(CH3 SO3 )2 -H2 O, and Mn(CH3 SO3 )2 -H2 O systems. Parameters of the Pitzer-Simonson-Clegg model were obtained in the Ni(CH3 SO3 )2 -H2 O, Co(CH3 SO3 )2 -H2 O, and Mn(CH3 SO3 )2 -H2 O systems. Several new hydrates in the Ni(CH3 SO3 )2 -H2 O, Co(CH3 SO3 )2 -H2 O, and Mn(CH3 SO3 )2 -H2 O systems were revealed. Stability parameters and crystal structures of the hydrates (Ni(CH3 SO3 )2 ·12H2 O, Ni(CH3 SO3 )2 ·6H2 O, Co(CH3 SO3 )2 ·4H2 O, Co(CH3 SO3 )2 ·9H2 O, Co(CH3 SO3 )2 ·6H2 O, Mn(CH3 SO3 )2 ·12H2 O, and Mn(CH3 SO3 )2 ·2H2 O) were calculated. Binary phase diagram fragments were calculated in the Ni(CH3 SO3 )2 -H2 O, Co(CH3 SO3 )2 -H2 O, and Mn(CH3 SO3 )2 -H2 O systems. Abstract: Solid-liquid equilibria in the Ni(CH3 SO3 )2 -H2 O, Co(CH3 SO3 )2 -H2 O, and Mn(CH3 SO3 )2 -H2 O systems were studied by isothermal solubility and DSC methods. TG and X-Ray diffraction were used to identify solid phases in equilibria with the solution. Water vapor pressure was determined by static method at 288.15 К, 298.15, and 308.15 K in the Ni(CH3 SO3 )2 -H2 O, Co(CH3 SO3 )2 -H2 O and Mn(CH3 SO3 )2 -H2 O systems. Based on vapor–liquid (VLE) and solid–liquid (SLE) equilibria data, parameters of the Pitzer-Simonson-Clegg model were obtained. Stability parameters of the hydrates Ni(CH3 SO3 )2 ·12H2 O, Ni(CH3 SO3 )2 ·6H2 O, Co(CH3 SO3 )2 ·4H2 O, Co(CH3 SO3 )2 ·9H2 O, Co(CH3 SO3 )2 ·6H2 O, Mn(CH3 SO3 )2 ·12H2 O, and Mn(CH3 SO3 )2 ·2H2 O were estimated. Binary phase diagram fragments were calculated.